Singer Working and Developing on the Voice - Makhmudov Jakhongir Saminjon ugli (Genius Journals, 2022)
This article deals with the voice of the singer, pedagogical methods and techniques in its formation, the rules of correct sound formation. There were also feedback on the work done on the singer’s voice, the competitions held to encourage and promote them, as well as to discover young, talented singers.
Keywords: Music; education; literacy; articulation